Comparison of Results between Hook Plate Fixation and Ligament Reconstruction for Acute Unstable Acromioclavicular Joint Dislocation - Yoon, Jong Pil; Lee, Byoung-Joo; Nam, Sang Jin; Chung, Seok Won; Jeong, Won-Ju; Min, Woo-Kie; Oh, Joo Han (Clinics in orthopedic surgery, 2015)
In the present study, we aimed to compare clinical and radiographic outcomes between hook plate fixation and coracoclavicular (CC) ligament reconstruction for the treatment of acute unstable acromioclavicular (AC) joint dislocation. Forty-two patients who underwent surgery for an unstable acute dislocation of the AC joint were included. We divided them into two groups according to the treatment modality: internal fixation with a hook plate (group I, 24 cases) or CC ligament reconstruction (group II, 18 cases). We evaluated the clinical outcomes using a visual analog scale (VAS) for pain and Constant-Murley score, and assessed the radiographic outcomes based on the reduction and loss of CC distance on preoperative, postoperative, and final follow-up plain radiographs. The mean VAS scores at the final follow-up were 1.6 ± 1.5 and 1.3 ± 1.3 in groups I and II, respectively, which were not significantly different. The mean Constant-Murley scores were 90.2 ± 9.9 and 89.2 ± 3.5 in groups I and II, respectively, which were also not significantly different. The AC joints were well reduced in both groups, whereas CC distance improved from a mean of 215.7% ± 50.9% preoperatively to 106.1% ± 10.2% at the final follow-up in group I, and from 239.9% ± 59.2% preoperatively to 133.6% ± 36.7% at the final follow-up in group II. The improvement in group I was significantly superior to that in group II (p < 0.001). Furthermore, subluxation was not observed in any case in group I, but was noted in six cases (33%) in group II. Erosions of the acromion undersurface were observed in 9 cases in group I. In cases of acute unstable AC joint dislocation, hook plate fixation and CC ligament reconstruction yield comparable satisfactory clinical outcomes. However, radiographic outcomes based on the maintenance of reduction indicate that hook plate fixation is a better treatment option.